Die Wiederkehr des Antiken in der Erzählung. Max Weber und Robert Musil: [The Return of Antiquity in Narrative Literature. Max Weber and Robert Musil] (Studia theodisca, 2017)
Max Weber and Robert Musil have shared interests, not only in analyzing the “modern world”. With contemporary philosophy having apparently become merely academic, and narration losing plausibility in history as well as in literature, they both choose the way of essayistic writing in order to substantiate their views. And in their search for a foundation they both go back to ancient philosophy, Weber to Plato and Musil to Plotinus.